STUDI KOMPARATIF HASIL BELAJAR SISWA ANTARA METODE TALKING CHIPS, TALKING STICK DAN GAYA BELAJAR EKONOMI PADA SISWA KELAS XI IPS SMA PGRI PEKANBARU: (Comparative Study Between Student Learning Method of Talking Chips, Talking Stick And Learning Styles in Economy Class XI IPS SMA PGRI Pekanbaru) - Dra.Hj.Tity Hastuti, M.Pd; Purba Andy Wijaya, M. Pd; Rahmeti Saumi (UIR Press, 2016)
This study aims to determine whether there are differences in learning outcomes of theeconomy between methods of talking chips and talking stick, find out if the learning outcomesof students' economic difference between students who have learning styles of visual, auditoryand kinesthetic, and find out if there is an interaction between methods and learning styles ininfluencing the results of the economic study. Samples are class XI IPS1 (Talking Chips) andXI IPS2 (Talking Stick). The method used quasi experiment with data analysis techniquesusing Two Way Annova. Measured using a student's learning style questionnaire learningstyles have tested the validity and reliability by previous research. Test student learningoutcomes using objective tests that have shaped the reliability of 0.847. Hypothesis testingresults show that there are differences in learning outcomes between methods of talking chipsand talking stick, where the results of studying methods of talking chips is higher than thetalking stick method. This is demonstrated by fhitung3,48> F table 3,17 at significance level α= 0.05. There is the influence of learning styles on student learning outcomes on economicsubjects, different between students who have a visual learning style, aiditorial andkinesthetic. This is demonstrated by fhitung7,37> F table 2,77 at significance level α = 0.05.And there is interaction between methods and learning styles to student learning outcomes oneconomic subjects. This is demonstrated by fhitung3,183> F table 2,77 at significance level α= 0.05. A further test using the Tukey which proves that there is a difference between learningoutcomes between methods chips and talking talking talking stick where the chips acquirehigher learning outcomes. While the visual learning style learning outcomes of economic gainhigher if taught with methods of talking chips and students who have auditory learning styleobtain a high learning outcomes when taught using Talking Stick.